Converts and the early development of Islam in Sabah: History and challenges from the 14th century to the independence era in 1963 - Zaifuddin Md Rasip; Nor Fatin Syuhaidah Nayan; Nor Iman Nabila Abu Bakar; Siti Hanisah Sabri; Mohd Zulfahmi Mohamad (Human Resource Management Academic Research Society, 2025)
This article discusses Muslim converts (muallaf) and the early development of Islam in Sabah, Malaysia, spanning from the 14th century to the attainment of independence in 1963. It examines key factors influencing the Islamization process, including trade, the roles of the Brunei and Sulu Sultanates, and the challenges faced during the colonial era. This study is crucial for understanding how Islam took root in Sabah's multicultural society, the role of muallaf in spreading Islam, and how this heritage shaped the religious and social identity of the local community. The primary objectives of this study are to analyze the role of maritime trade in introducing Islam to Sabah, to elucidate the contributions of the Brunei and Sulu Sultanates in strengthening Islamic influence, to evaluate the role of muallaf as agents of da'wah, and to assess the challenges and opportunities faced by the Muslim community during the colonial period up to independence. The study employs a qualitative approach using historical analysis, focusing on literature reviews. Data were obtained from academic journals, books, articles, and reports related to the early development of Islam in Sabah. This approach involves descriptive and thematic analyses to examine patterns and factors influencing the spread of Islam in Sabah. The findings indicate that Islam was introduced to Sabah through Arab and Chinese Muslim traders, further reinforced by the roles of the Brunei and Sulu Sultanates, as well as the contributions of local muallaf and ulama. The challenges posed by British colonial rule, which prioritized Christian missions, were effectively addressed through the resilience of religious institutions, efforts by local ulama, and the determination of muallaf in upholding their faith and spreading Islamic teachings. This study aims to enrich the understanding of Sabah’s Islamic history and serve as a reference for developing more inclusive and effective da'wah strategies for multicultural societies.